1987
DOI: 10.1111/j.1472-8206.1987.tb00570.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SOME TRICYCLIC AND NONTRICYCLIC ANTIDEPRESSANTS ON [3H]IMIPRAMINE BINDING AND SEROTONIN UPTAKE IN RAT CEREBRAL CORTEX AFTER PROLONGED TREATMENT

Abstract: Chronic administration of different antidepressant drugs reduced the number of [3H]imipramine [( 3H]IMI) binding sites in rat cerebral cortex. In the same experimental conditions, fluvoxamine and dothiepin, as well as desmethylimipramine, induced an increase in the maximal velocity of high affinity serotonin (5HT) uptake in cortical slices, whereas citalopram and viloxazine were ineffective in this regard. Our results indicate that even if 5HT uptake and [3H]IMI binding sites are located on the same nerve term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Chronic treatment with DMI has been shown to induce a down regulation of )H-IMI binding sites (Barbaccia et al 1983a;Brunello et al 1987); and this effect, as shown in fig. 1, was still present in aged rats, where the prolonged administration with the antidepressant drug reduced the density of ?H-IMI recognition sites to the same extent as in young adult animals.…”
Section: Adults Ratsmentioning
confidence: 89%
See 1 more Smart Citation
“…Chronic treatment with DMI has been shown to induce a down regulation of )H-IMI binding sites (Barbaccia et al 1983a;Brunello et al 1987); and this effect, as shown in fig. 1, was still present in aged rats, where the prolonged administration with the antidepressant drug reduced the density of ?H-IMI recognition sites to the same extent as in young adult animals.…”
Section: Adults Ratsmentioning
confidence: 89%
“…Adaptive changes occur also in serotonergic system after a chronic treatment with antidepressants: down-regulation of 5-HT postsynaptic receptors has been reported by several authors (Peroutka & Snyder 1980;Dumbrille Ross et al 1982;Friedman et al 1986) and the density of 3H-IMI recognition sites. located on serotonergic nerve terminals, seem to undergo a down-regulation after a prolonged administration with antidepressants (Raisman et al 1980;Barbaccia et al 1983a;Brunello et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies performed in experimental animals had suggested that the [3H]IMI binding site may modulate the presynaptic uptake of 5-HT in an inhibitory way (Costa et al, 1983). In fact, drugs able to displace labeled IMI also inhibit the highaffinity 5-HT uptake (Langer et al, 1 9 8 0~)~ and the prolonged exposure to some antidepressants induces concomitantly the decrease in Bma, of [3H]IMI binding and the increase in V,,, of 5-HT uptake (Barbaccia et al, 1983;Brunello et al, 1987). Moreover, during aging, the two sites undergo opposite modifications, because the density of [3H]IMI binding sites is increased in 24-month-old animals, whereas, at the same age, the V,,, of 5-HT uptake is decreased (Brunello et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Chamba et al (1991) showed indeed that 5-HT platelet uptake remained increased even after chronic administration of tianeptine (+14% on day 10 and +13% on day 28, as compared with +23% two hours after acute dose). Interestingly, Brunello et al (1987) described that after chronic administration, even fluvoxamine and dothiepine, as well as DMI induced an increase in the maximal velocity of high affinity serotonin uptake in cortical slices. Finally, Invernizzi et al (1992) and Sacchetti et al (1993) demonstrated that tianeptine increased extracellular dopamine and blocked the stress-induced increase in noradrenaline release in the frontal cortex.…”
Section: Discussionmentioning
confidence: 97%